Effects of Inhalation of Acidic Compounds on Pulmonary Function in Allergic Adolescent Subjects - Koenig, Jane Q.; Covert, David S.; Pierson, William E. (Environmental health perspectives, 1989)
There is concern about the human health effects of inhalation of acid compounds found in urban air pollution. It was the purpose of this study to investigate three of these acid compounds, sulfur dioxide ( SO2), sulfuric acid ( H2SO4), and nitric acid ( HNO3) in a group of allergic adolescent subjects. Subjects were exposed during rest and moderate exercise to 0.7 μ mole/ m3(68 μ g/ m3) H2SO4, 4.0 μ mole/ m3(0.1 ppm) SO2, or 2.0 μ mole/ m3(0.05 ppm) HNO3. Pulmonary functions ( FEV1, total respiratory resistance, and maximal flow) were measured before and after exposure. Preliminary analysis based on nine subjects indicates that exposure to 0.7 μ mole/ m3H2SO4alone and in combination with SO2caused significant changes in pulmonary function, whereas exposure to air or SO2alone did not. FEV1decreased an average of 6% after exposure to H2SO4alone and 4% when the aerosol was combined with SO2. The FEV1decrease was 2% after both air and SO2exposures. Total respiratory resistance (RT) increased 15% after the combined H2SO4exposures, 12% after H2SO4alone, and 7% after exposure to air. After exposures to HNO3alone, FEV1decreased by 4%, and RTincreased by 23%. These results are preliminary; final conclusions must wait for completion of the study.